Transplanting Cotton: A novel technique for enhancing productivity and resource use efficiency - Rana, D S; Paul, Tarun; Rajput, Sudhir (Indian Farming, 2015)
Transplanting of cotton is novel technique for enhancing the productivity, profitability and resource use efficiency and thus for improving the livelihood security of small holders. This agro-technique has also been found more economical and can go a long way in sustaining and increasing the cotton productivity.